Competition when Consumers have Switching Costs: An Overview with Applications to Industrial Organization, Macroeconomics, and International Trade - Klemperer, P. (Review of Economic Studies, 1995)
We survey recent work on competition in markets in which consumers have costs of switching between competing firms' products, even when all firms' products are functionally identical. We address issues in macroeconomics and international trade, as well as industrial organization: In a market with switching costs (or 'brand loyalty'), a firm's current market share is an important determinant of its future profitability. We examine how the firm's choice between setting a low price to capture market share, and setting a high price to Harvest profits by exploiting its current locked-in customers, is affected by the threat of new entry interest rates, exchange rate expectations, the state of the business cycle, etc. We also discuss the causes of switching costs, explain introductory offers and price wars, and examine industry profits, firms' product choices, and implications for multi-product competition. Copyright 1995 by The Review of Economic Studies Limited.